Possible roles of phytochemicals with bioactive properties in the prevention of and recovery from COVID-19 - Koyama, Sachiko; Joseph, Paule V.; Shields, Vonnie D. C.; Heinbockel, Thomas; Adhikari, Poonam; Kaur, Rishemjit; Kumar, Ritesh; Alizadeh, Rafieh; Bhutani, Surabhi; Calcinoni, Orietta; Mucignat-Caretta, Carla; Chen, Jingguo; et al. (Frontiers in Nutrition, 2024)
There have been large geographical differences in the infection and death rates of COVID-19. Foods and beverages containing high amounts of phytochemicals with bioactive properties were suggested to prevent contracting and to facilitate recovery from COVID-19. The goal of our study was to determine the correlation of the type of foods/beverages people consumed and the risk reduction of contracting COVID-19 and the recovery from COVID-19. We developed an online survey that asked the participants whether they contracted COVID-19, their symptoms, time to recover, and their frequency of eating various types of foods/beverages. The survey was developed in 10 different languages. The participants who did not contract COVID-19 consumed vegetables, herbs/spices, and fermented foods/beverages significantly more than the participants who contracted COVID-19. Among the six countries (India/Iran/Italy/Japan/Russia/Spain) with over one hundred participants and high correspondence between the location of the participants and the language of the survey, in India and Japan the people who contracted COVID-19 showed significantly shorter recovery time, and greater daily intake of vegetables, herbs/spices, and fermented foods/beverages was associated with faster recovery. Our results suggest that phytochemical compounds included in the vegetables may have contributed in not only preventing contraction of COVID-19, but also accelerating their recovery.